2013
DOI: 10.1038/jcbfm.2013.214
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Oxygen Metabolism in Neonates with Congenital Heart Disease Quantified by MRI and Optics

Abstract: Neonatal congenital heart disease (CHD) is associated with altered cerebral hemodynamics and increased risk of brain injury. Two novel noninvasive techniques, magnetic resonance imaging (MRI) and diffuse optical and correlation spectroscopies (diffuse optical spectroscopy (DOS), diffuse correlation spectroscopy (DCS)), were employed to quantify cerebral blood flow (CBF) and oxygen metabolism (CMRO 2 ) of 32 anesthetized CHD neonates at rest and during hypercapnia. Cerebral venous oxygen saturation (S v O 2 ) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
192
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(219 citation statements)
references
References 52 publications
6
192
5
Order By: Relevance
“…A similar trend is observed with our MRI results, showing a decreased CMRO2 relative to healthy subjects examined with a similar technique (8), and slightly higher CMRO2 than in anesthetized subjects (4,11) (Figure 2). SvO2 and OEF measurements correlate across modalities (r 2 =0.596, p=0.015 for SvO2; r 2 =0.525, p=0.027 for OEF) suggesting that these measures capture similar information and/or are relatively stable in this cohort (Figure 3).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…A similar trend is observed with our MRI results, showing a decreased CMRO2 relative to healthy subjects examined with a similar technique (8), and slightly higher CMRO2 than in anesthetized subjects (4,11) (Figure 2). SvO2 and OEF measurements correlate across modalities (r 2 =0.596, p=0.015 for SvO2; r 2 =0.525, p=0.027 for OEF) suggesting that these measures capture similar information and/or are relatively stable in this cohort (Figure 3).…”
Section: Discussionsupporting
confidence: 78%
“…The etiology of neurodevelopmental disorders is unknown but evaluation of the hemodynamic state of CHD infants pre-and post-surgically has become a focus with cerebral metabolic rate of oxygen consumption (CMRO2) identified as a key parameter for clinical evaluation (2-5). Jain et al (4) demonstrated correlations between magnetic resonance imaging (MRI) and near-infrared spectroscopy (NIRS) measures of CMRO2 pre-surgically when measured simultaneously in anesthetized neonates. We present NIRS and MRI-based measures of cerebral hemodynamics (OEF, CBF and CMRO2) in nine stable neonates with CHD.…”
Section: Introductionmentioning
confidence: 99%
“…When combined with CBF measurements by PC MRI and ASL, MR oximetry techniques can provide noninvasive quantification of global and regional CMRO 2 , respectively. In particular, global OEF and CMRO 2 measurement has been shown to be fast and reliable, and has shown clinical utility in neonatal imaging (De Vis et al, 2014;Jain et al, 2014;Liu et al, 2014). The developmental trajectories of global CBF, OEF and CMRO 2 at baseline observed in the present study are in excellent agreement with existing PET literature on developmental curves of CBF, CMRglu and CMRO 2 (Chiron et al, 1992;Chugani, 1998;Takahashi et al, 1999;Wintermark et al, 2004).…”
Section: Developmental Trajectories Of Cbf and Cmro 2 At Baselinesupporting
confidence: 82%
“…In particular, relative changes in CBF i due to hypercapnia correlated well with relative changes in blood flow in the common jugular veins and superior vena cava [40], and with perfusion arterial spin-labeling MRI [39,41]. More recently, baseline CBF i was also validated with baseline perfusion MRI in CHD [41].…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have shown that simultaneous FDNIRS-DCS and MRI measures of cerebral blood flow and cerebral oxygen metabolism correlate well in anesthetized, preoperative CHD neonates [39][40][41]. In particular, relative changes in CBF i due to hypercapnia correlated well with relative changes in blood flow in the common jugular veins and superior vena cava [40], and with perfusion arterial spin-labeling MRI [39,41].…”
Section: Introductionmentioning
confidence: 99%